Interdisciplinary measurement: A systematic review of the case of sustainability. (May 2020) - Brink, Matthijs; Hengeveld, Geerten M.; Tobi, Hilde
Highlights: Interdisciplinary measurement of sustainability in the TBL framework is near-unique. Reports of interdisciplinary measurement models are often incomplete. Low measurement levels occur in environmental, social and economic indicators. Composite measures often combine different or unknown measurement levels. Weighting schemes to reach composite measurements are often based on expert opinion. Abstract: Measurement in interdisciplinary research can be difficult due to incompatibility of measures used in the different disciplines. These difficulties arise when measurements from different disciplines need to be combined to quantify an attribute for an object of study. Sustainability is a fuzzy concept measured as an attribute of many different objects. Sustainability measurements are often a composition of environmental, economic and social sustainability measurements, which makes them interdisciplinary composite measurements. The present study aims to advance interdisciplinary sustainability research by a systematic review of the interdisciplinary measurement of the attribute sustainability using the Triple Bottom Line (TBL) framework and to investigate whether measurement issues differ between the environmental, economic and social dimension. A systematic literature review was done based on a query, on Web of Science, that reflected the interdisciplinarity of sustainability science and the TBL framework. Abstracts were scanned for relevance and papers that passed the scan were downloaded and scrutinized for their measurement characteristics such as measurement level, aggregation of scores into composite measurements, and weighting methods. An iterative coding approach (top-down and bottom-up) was used until saturation was reached. The search returned 467 papers, of which 77 contained sufficiently detailed information on the interdisciplinary measurement of sustainability, following the TBL framework. Not all papers in the final set contained sufficiently detailed information on the performed measurements, and if and how the distinct dimensions were combined into one interdisciplinary sustainability measurement. The 86 reported measurement models of sustainability were heterogeneous with respect to measurement levels used, the use of composite scores, weighting schemes and time synchronization between indicators. Two thirds of the measurement models presented composite scores of the attribute sustainability. The weights used in composite scores were in most cases determined using experts' opinions. Albeit all included papers used the TBL as a framework, their measurement models do not form a coherent set. Fuzzy measurement practices occurred in all three dimensions of sustainability. On closer inspection, and wherever reports were sufficiently specific, interdisciplinary measurement models of sustainability turned out to be near-unique.